A new nemertean species: what are the useful characters for ribbon worm descriptions?. (March 2014) - Strand, Malin; Herrera-Bachiller, Alfonso; Nygren, Arne; Kånneby, Tobias
<x content-type="archive" xml:space="preserve">Abstract</x> In recent years the Norwegian Taxonomy Initiative started thorough investigations of poorly known organism groups. In this context, several marine inventories have rendered a number of marine invertebrate species new to science. Within the phylum Nemertea (ribbon worms) a characteristic hoplonemertean was encountered on two different occasions. We describe the new species Amphiporus rectangulus sp. nov. with a combination of histology and DNA data (COI). For the morphological description we use a previously proposed character matrix and, in a context given by the results, also provide a brief discussion on benefits and drawbacks with both methods. We argue that for small animals with soft bodies external characters can be more informative than hitherto expected.